Kajian Taman Abhirama Sidoarjo Berdasarkan Elemen Desain Aktif - Gita Khoirin Nisa; Bambang Soemardiono; Ima Defiana (Universitas Sebelas Maret Surakarta, 2023)
Urban parks are integral components of Green Open Spaces (GOS) with a significant impact on community well-being. This study integrates urban parks with an active design approach to promote physical activity. The research aims to identify active design elements within Abhirama Park, located in Sidoarjo Regency. The choice of active design is based on previous research demonstrating its potential to encourage greater community engagement. The results of this identification and analysis can serve as a reference for future developments of Abhirama Park, with the goal of creating Green Open Spaces that stimulate physical activity in an era characterized by sedentary lifestyles driven by digital advancements. This study employs a qualitative descriptive method, involving naturalistic exploration and in-depth examination of the subject. Active design guidelines are used as a framework during the observation and interview processes. The findings reveal the presence of four active design aspects in Abhirama Park: Accessibility, Facilities, Activities, and Management. Each aspect plays a distinct role in promoting physical activity within the urban context.